Maria, Maria : and other stories - Rubio, Marytza K. (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2022)
"For fans of Kali Fajardo-Anstine and Lesley Nneka Arimah, a darkly funny and imaginative debut conjuring tales of Mexican American mystics and misfits. "The first witch of the waters was born in Destruction. The moon named her Maria." From former PEN America Emerging Voices Fellow Marytza K. Rubio comes Maria, Maria, an inimitable collection set across the tropics and megacities of the Americas. Readers will be enticed and infuriated as characters negotiate with nature to cast their desired ends-such as the enigmatic community college professor in "Brujeria for Beginners'; the disturbingly faithful widow in "Tijuca"; and the lonely little girl in "Burial," who awakens a sabretooth tiger. Brimming with sharp wit and ferocious female intuition, the book bubbles over into a novella of fantastical proportions-a "tropigoth" family drama set in a reimagined California micro-rainforest about the legacies of three Marias, possibly all Marias. Writing in prose so lush it threatens to creep off the page, Rubio emerges as a bold voice new voice in contemporary short fiction"--